2005
DOI: 10.1371/journal.pmed.0020246
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory Attitudes and Practices by Health Workers toward Patients with HIV/AIDS in Nigeria

Abstract: BackgroundNigeria has an estimated 3.6 million people with HIV/AIDS and is home to one out of every 11 people with HIV/AIDS worldwide. This study is the first population-based assessment of discrimination against people living with HIV/AIDS in the health sector of a country. The purpose of this study was to characterize the nature and extent of discriminatory practices and attitudes in the health sector and indicate possible contributing factors and intervention strategies. The study involved a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
187
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(212 citation statements)
references
References 16 publications
18
187
2
5
Order By: Relevance
“…Generally, participants acknowledged that the magnitude of stigma and/or discrimination has greatly decreased compared with previous years. As in previous studies (Surlis & Hyde, 2001;Letamo, 2005;Reis et al, 2005;Mahendra et al, 2007;Feyissa et al, 2012;Ekstrand et al, 2013), this study found some variation in the causes of stigma and discrimination in health care settings. It confirms that existing stigma and discrimination in society, transmission-related fear and institutional policies on HIV management, as well as lack of proper knowledge of HIV amongst health care workers not directly involved in the treatment of SSA migrant women with HIV, drive and endorse stigma feelings and discriminatory attitudes.…”
Section: Discussionsupporting
confidence: 76%
“…Generally, participants acknowledged that the magnitude of stigma and/or discrimination has greatly decreased compared with previous years. As in previous studies (Surlis & Hyde, 2001;Letamo, 2005;Reis et al, 2005;Mahendra et al, 2007;Feyissa et al, 2012;Ekstrand et al, 2013), this study found some variation in the causes of stigma and discrimination in health care settings. It confirms that existing stigma and discrimination in society, transmission-related fear and institutional policies on HIV management, as well as lack of proper knowledge of HIV amongst health care workers not directly involved in the treatment of SSA migrant women with HIV, drive and endorse stigma feelings and discriminatory attitudes.…”
Section: Discussionsupporting
confidence: 76%
“…Negative attitudes towards HIV-infected colleagues were also noted in previous studies in Nigeria, in which 43.6% of the HCWs studied were uncomfortable being assisted by an infected colleague, and 51.1% were uncomfortable sharing a bathroom with an infected colleague (Aisien & Shobowale, 2005). In another study (Reis et al, 2005), 40% of HCWs believed that infected HCWs should not be allowed to work in any area of health care that requires patient contact.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented negative attitudes to PLWHA in health care settings in Nigeria and elsewhere (Adelekan et al, 1995;Fido & Al Kamezi, 2002;Hentgen, Jaureguiberry, Ramiliarisoa, Andrianantoandro & Belec, 2002;Quach, Mayer, McGarvey, Lurie & Do, 2005;Reis et al, 2005). Physicians and nurses have been reported to be uncomfortable when administering medical procedures to HIV-infected patients (Oyeyemi, Oyeyemi & Bello, 2006;Oyeyemi, Oyeyemi & Bello, 2008), while in one study (Fransman, McCulloch, Lavies & Hussey, 2000) more than half of respondents were found to be reluctant to perform invasive procedures on HIV-infected children.…”
Section: Introductionmentioning
confidence: 99%
“…12,20,21 Similarly, studies from several countries identified the various factors affecting stigmatized and discriminatory attitudes toward PLWHA among Health Care Workers to include level of irrational fear of HIV transmission, level of education, gender, stage of the disease, high-risk taking behaviour, individuals related to stigmatized identities, sources of HIV infection, relationship with an infected person, type of hospital, ethnicity and urbanrural locality. 22,23 To date, with the increasing knowledge of modes of transmission and infection-control measures, guidelines have now been established to ensure that staff and patients are adequately protected within the last decade. Unfortunately, it is believed that much fear and ignorance still exist.…”
Section: Introductionmentioning
confidence: 99%